Isolation and characterization of shiga toxin-producing Escherichia coli O157:H7 from cattle feces within Zaria Metropolis, Nigeria - ABDULRAZAK LAWAL; Lawan Kabir; Fatima Balarabe; Yusuf Abubakar; Mannir Usman; Fatima Lawal; Yuguda Umar (Microbes and Infectious Diseases)
Background: Shiga toxin-producing Escherichia coli (STEC) O157:H7 is a significant zoonotic pathogen implicated in severe human illnesses such as hemorrhagic colitis and hemolytic uremic syndrome (HUS). Cattle are known asymptomatic reservoirs, and their fecal shedding of the pathogen poses a public health risk through contamination of food and water sources. This study aimed to isolate and molecularly characterize STEC O157:H7 from cattle feces within Zaria Metropolis, Nigeria. Methods: A cross sectional study was conducted. A total of 328 cattle faecal samples were collected from Eight (8) different Fulani cattle herds. Faecal samples where enriched, selectively cultured, and screened for E. coli O157:H7 using Wellcolex rapid latex agglutination kit and multiplex polymerase chain reaction (PCR) to detect stx1, stx2, eaeA and hlyA genes. Results: A total of 26 (7.93%) isolates were positive for E. coli O157:H7 using Wellcolex rapid latex agglutination kit. Out of which, 1(0.31%) isolate was found in bull while 25(7.62%) were in cows, 3(0.91%) isolates were in calves while 23(7.02%) in adult cattle and 4(1.22%) were in Bokoloji while 22(6.71%) were in Bunaji, a total 26 isolates were subjected to multiplex PCR, only 2(7.69%) expressed the shiga toxin genes (stx1). Conclusion: This study highlights the presence of shiga toxin producing E. coli O157:H7 in the cattle population of Zaria and the need for stringent control measures to prevent transmission to humans.